If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18(7-2n)=1(7+2n)
We simplify the equation to the form, which is simple to understand
18(7-2n)=1(7+2n)
Reorder the terms in parentheses
+(+126-36n)=1*(7+2n)
Remove unnecessary parentheses
+126-36n=+1+*(+7+2n+)
Reorder the terms in parentheses
+126-36n=+(+7+2n)
Remove unnecessary parentheses
+126-36n=+7+2n
We move all terms containing n to the left and all other terms to the right.
-36n-2n=+7-126
We simplify left and right side of the equation.
-38n=-119
We divide both sides of the equation by -38 to get n.
n=3.13157894737
| 3+2p=17 | | 3x+4=28x-78 | | 4x+42-5x=2-8x-5 | | 747=2.4x^2+90.8x+1.59 | | X^3+X^2=576 | | 4t=1.6 | | -13t=-117 | | x-10y=-10 | | B-7.5=1 | | 160=112t-16t | | 6-p=5p+30 | | T-2.2=3.1 | | -3c=3 | | 9w=5(w-14) | | 25x^3-5x^2+8x+2=0 | | -21=y+y+y | | 7.5=m+5 | | N+1.6=2.8 | | -2(5-7x)=-150 | | 81u^2-u^2v^4= | | 15=6n | | 6(8+a)=15(1+a) | | 7x-2x=x+9+x | | 6x-(4x+7)=14-5 | | -3c=-117 | | y-2x+4=-7x+4x^2 | | 5t=6 | | 6x+2x=10x+12-4x | | 2n+5(2n+3)= | | 700+60x=400+60x | | 117-7x=20x-21 | | 10(x-5)=3(x+2) |